Blocking histone methyltransferase SETDB1 inhibits tumorigenesis and enhances cetuximab sensitivity in colorectal cancer. (1st September 2020) - Hou, Zhenlin; Sun, Li; Xu, Feng; Hu, Fuqing; Lan, Jingqin; Song, Da; Feng, Yongdong; Wang, Jing; Luo, Xuelai; Hu, Junbo; Wang, Guihua
Abstract: The histone methyltransferase SETDB1 catalyzes the addition of methyl groups to histone H3 at lysine 9, and upregulation of SETDB1 is associated with poor prognosis in cancer patients. Here, we describe how overexpression of SETDB1 contributes to colorectal cancer (CRC) tumorigenesis and drug resistance. We show that SETDB1 is upregulated in CRC, and its level correlates with poor clinical outcome. SETDB1 attenuation inhibits CRC cell proliferation Mechanistically, SETDB1 promotes cell proliferation by upregulating Akt activation. Further, SETDB1 is essential for the tumorigenic activity of Akt. Functional characterization revealed that inhibition of SETDB1 reduces cell growth in CRC resistant to targeted treatments in vitro and in vivo, KRAS-mutated CRC included. Taken together, our results indicate that SETDB1 is a major driver of CRC and may serve as a potential target for the treatment of KRAS-mutated CRC. Highlights: Our study identifies that SETDB1 is a major driver of CRC and may serve as a potential future target for the treatment of KRAS mutant CRC.